A General Access to Propargylic Ethers through Brønsted Acid Catalyzed Alkynylation of Acetals and Ketals with Trifluoroborates . Issue 39 (6th August 2015) - Baxter, Matthew; Bolshan, Yuri
Abstract A general Brønsted acid catalyzed methodology for the alkynylation of acetals and ketals with alkynyltrifluoroborate salts has been developed. The reaction proceeds rapidly to afford valuable synthetic building block propargylic ethers in good to excellent yields. Unlike Lewis acid catalyzed transformations of trifluoroborates, this approach does not proceed via unstable organodifluoroborane intermediate. As a result, the developed methodology features excellent functional group tolerance and good atom economy.